Prognostic factors in patients with vulvar cancer: the VULCAN study. Issue 9 (September 2020) - Zapardiel, Ignacio; Iacoponi, Sara; Coronado, Pluvio J; Zalewski, Kamil; Chen, Frank; Fotopoulou, Christina; Dursun, Polat; Kotsopoulos, Ioannis C; Jach, Robert; Buda, Alessandro; Martinez‐Serrano, Maria J; Grimm, Christoph; et al.
ABSTRACT : Objective : This study aimed to analyze the prognostic factors for overall and progression‐free survival in patients with vulvar cancer. Methods : This international, multicenter, retrospective study included 2453 patients diagnosed with vulvar cancer at 100 different institutions. Inclusion criteria were institutional review board approval from each collaborating center, pathologic diagnosis of invasive carcinoma of the vulva, and primary treatment performed at the participating center. Patients with intraepithelial neoplasia or primary treatment at non‐participating centers were excluded. Global survival analysis and squamous cell histology subanalysis was performed. Results : After excluding patients due to incomplete data entry, 1727 patients treated for vulvar cancer between January 2001 and December 2005 were registered for analysis (1535 squamous, 42 melanomas, 38 Paget's disease and 112 other histologic types). Melanomas had the worse prognosis (p=0.02). In squamous vulvar tumors, independent factors for increase in local recurrence of vulvar cancer were: no prior radiotherapy (p<0.001) or chemotherapy (p=0.006), and for distant recurrence were the number of positive inguinal nodes (p=0.025), and not having undergone lymphadenectomy (p=0.03) or radiotherapy (p<0.001), with a HR of 1.1 (95% CI 1.2 to 1.21), 2.9 (95% CI 1.4 to 6.1), and 3.1 (95% CI 1.7 to 5.7), respectively. Number of positive nodes (p=0.008), FIGO stage (p<0.001), adjuvant chemotherapy (p=0.001), tumor resection margins (p=0.045), and stromal invasion >5 mm (p=0.001) were correlated with poor overall survival, and large case volume (≥9 vs <9 cases per year) correlated with more favorable overall survival (p=0.05). Conclusions : Advanced patient age, number of positive inguinal lymph nodes, and lack of adjuvant treatment are significantly associated with a higher risk of relapse in patients with squamous cell vulvar cancer. Case volume per treating institution, FIGO stage, and stromal invasion appear to impact overall survival significantly. Future prospective trials are warranted to establish these prognostic factors for vulvar cancer.